Early Life in a Barren Environment Adversely Affects Spatial Cognition in Laying Hens (Gallus gallus domesticus) - Tahamtani, Fernanda M.; Nordgreen, Janicke; Nordquist, Rebecca E.; Janczak, Andrew M. (Frontiers in Veterinary Science, 2015)
Spatial cognition in vertebrates is adversely affected by a lack of environmental complexity during early life. However, to our knowledge no previous studies have tested the effect of early exposure to varying degrees of environmental complexity on specific components of spatial cognition in chickens. There are two main rearing systems for laying hens in the EU: aviaries and cages. These two systems differ from one another in environmental complexity. The aim of the present study was to test the hypothesis that rearing in a barren cage environment relative to a complex aviary environment causes long-lasting deficits in the ability to perform spatial tasks. For this purpose, 24 white Dekalb laying hens, half of which had been reared in an aviary system and the other half in a conventional cage system, were tested in a holeboard task. Birds from both treatment groups learnt the task, however the cage-reared hens required more time to locate rewards and had poorer levels of working memory. The latter finding supports the hypothesis that rearing in a barren environment causes long-term impairment of short-term memory in chickens.